Klasifikasi Pertumbuhan, Sektor Basis dan Kompetitif Kota Jambi - Yusral Yusral; Junaidi Junaidi; Adi Bhakti (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2015)
This study aims to determine the classification of economic growth in the city of Jambi, base and non-base sectors in the economy of the city of Jambi, Competitive sectors in the economy of the city of Jambi and to determine the leading sectors in Jambi city.The results showed that based on the analysis tipology Klassen, there are three (3) sectors forward and grow exponentially (quadrant I), namely manufacturing industry, trade sector, hotel and restaurant as well as transport and communication sectors. During the period 2000-2012 the leading sectors in the city of Jambi based analysis of location Quetiont (LQ) there are as many as seven sectors, namely Manufacturing (LQ = 1.37), sector Electricity, Gas and Water (LQ = 3.25), Construction sector (LQ = 1.61), the sector of Trade, Hotels and Restaurants (LQ = 1.38), transport and communications sector (LQ = 2.52), Financial sector, Leasing & Business Services (LQ = 1.76) Offices and Services sector (LQ = 1.44). Based Shift Share Analysis for the period 2000-2012, the sectors that possess proporsioal growth component value (P) positive namely Mining and Quarrying sector, sectors Electricity Gas and Water, Building sector, the hotel and restaurant trade sector, as well as the financial sector, leasing and services company. Sectors which show the value of diffrential Shift (D) is positive Manufacturing sector, trade sector, hotel and restaurant as well as transport and communications sectors. Based on a combined analysis of three tools of analysis shows that the sector is the dominant sector in the sector that belong criteria developed and grown by leaps and bounds, and competitive sector basis is the sector of Trade, Hotels and Restaurants.